Molecular analyses of groundwater amphipods (Crustacea: Niphargidae) from Luxembourg: new species reveal limitations of morphology-based checklists - Weber, Dieter; Flot, Jean-François; Frantz, Alain C.; Weigand, Alexander M. (Zootaxa, 2022)
Niphargus amphipods were collected from 2007 to 2018 at 98 sites comprising artificial caverns, springs and interstitial waters in the Grand Duchy of Luxembourg. Opportunistic sampling was combined with passive trapping. Specimen identification was achieved using morphological keys and molecular data. Initial morphological determination and literature data suggested five species, whereas sequencing of fragments of the mitochondrial cytochrome c oxidase subunit 1 gene and nuclear 28S rDNA marker supported the presence of seven species: Niphargus schellenbergi, Niphargus puteanus, Niphargus fontanus, one species of the Niphargus kochianus complex, and three species of the Niphargus aquilex complex. Niphargus schellenbergi was by far the most abundant and widespread species. Limited overlap was observed between literature-based records, our initial morphological determinations based on classical taxonomic characters, and genetic sequence data. In general, the combination of phenotypically variable taxa, such as N. schellenbergi, and cryptic or near-cryptic species, as in the N. aquilex complex, renders morphological identification of niphargids from Luxembourg a challenging or even impossible task. DNA taxonomy will therefore have to be used in future studies of the fauna of this region.